Genetic buffering of cyclic AMP in Arabidopsis thaliana compromises the plant immune response triggered by an avirulent strain of Pseudomonas syringae pv. tomato. (12th March 2019) - Sabetta, Wilma; Vandelle, Elodie; Locato, Vittoria; Costa, Alex; Cimini, Sara; Bittencourt Moura, Andrea; Luoni, Laura; Graf, Alexander; Viggiano, Luigi; De Gara, Laura; Bellin, Diana; Blanco, Emanuela; et al.
Summary: Cyclic AMP plays important roles in different physiological processes, including plant defence responses. However, as little information is known on plant enzymes responsible for cAMP production/degradation, studies of cAMP functions have relied, to date, on non‐specific pharmacological approaches. We therefore developed a more reliable approach, producing transgenic Arabidopsis thaliana lines overexpressing the 'cAMP‐sponge' (cAS), a genetic tool that specifically buffers cAMP levels. In response to an avirulent strain of Pseudomonas syringae pv. tomato ( PstAvrB ), cAS plants showed a higher bacterial growth and a reduced hypersensitive cell death in comparison with wild‐type (WT) plants. The low cAMP availability after pathogen infection delayed cytosolic calcium elevation, as well as hydrogen peroxide increase and induction of redox systems. The proteomic analysis, performed 24 h post‐infection, indicated that a core of 49 proteins was modulated in both genotypes, while 16 and 42 proteins were uniquely modulated in WT and cAS lines, respectively. The involvement of these proteins in the impairment of defence response in cAS plants is discussed in this paper. Moreover, in silico analysis revealed that the promoter regions of the genes coding for proteins uniquely accumulating in WT plants shared the CGCG motif, a target of the calcium‐calmodulin‐binding transcription factor AtSR1 ( Arabidopsis thaliana signal responsive1). Therefore, following pathogen perception, the low free cAMP content, altering timing and levels of defence signals, and likely acting in part through the mis‐regulation of AtSR1 activity, affected the speed and strength of the immune response. Significance Statement: This study introduces the use of the cAMP‐sponge as a genetic tool to investigate the role of cAMP in plant immune responses, revealing the complexity of the signal network involved in the establishment of plant resistance against an avirulent strain of Pseudomonas syringae pv. tomato . The decrease in free cAMP content, altering the timing and levels of cytosolic calcium and hydrogen peroxide signals upon pathogen perception, affected the speed and strength of the immune response.